The relationship between gender, psychosocial factors, pain, health literacy and health-related quality of life in parents of Norwegian adolescents one year into the COVID-19 pandemic - Gudrun Rohde; Sølvi Helseth; Milada Hagen; Hilde Timenes Mikkelsen; Siv Skarstein; Kristin Haraldstad (BMC, 2024)
Abstract Background Stress impacts healthy behaviours and may influence life and health-related quality of life (HRQOL). A stressful event occurred when the COVID-19 pandemic hit in March 2020. The present study aims to explore possible gender differences in stress, psychosocial factors (self-efficacy, self-esteem, loneliness), pain, HL, and HRQOL in parents of adolescents one year into the COVID-19 pandemic, and to explore possible associations between gender, demographic and psychosocial factors, pain, HL, and HRQOL. Methods Parents of adolescents aged 16-17 took part in the study from January to February 2021, when the COVID-19 pandemic was ongoing. Data on socio-demographics, stress, self-efficacy, self-esteem, pain, HL, loneliness, and HRQOL were collected. HRQOL was assessed using RAND-36. Results Among the 320 parents from the general population, the mean age was 47.6 (standard deviation (SD) = 4.6) years, 81% were mothers, 79% were married or cohabiting, 81% had a university degree, and the majority worked full time (78%) or part time (13%). The average pain score was low, 0.48 (95% CI [0.43-0.54]). However, 50% of the parents reported persistent pain and more mothers reported persistent pain compared to fathers (53% vs. 37%). The parents' mean (SD) score for RAND-36 was 52.1 (95% CI [51.2-53.0]) for the physical component summary (PCS) score and 51.0 (95% CI [50.0-52.1]) for the mental component summary (MCS) score. Mothers reported significantly lower scores for all the eight RAND-36 domains and the PCS and MCS scores. Adjusting for gender, age, living condition, education, pain, HL, self-efficacy and loneliness, we revealed no associations between stress and RAND-36-PCS. University education of four years or more was positively associated (B = 3.29, 95% CI: [0.78-5.80]) with RAND-36-PCS, while persistent pain was negatively associated (B = -7.13, CI: [-9.20- -5.06]). We identified a strong negative association between RAND-36-MCS and stress (B = -43.11, CI: [-48.83- -37.38]) and a positive association with older age (B = 0.21, CI: [ 0.04, 0.39)]. Conclusion One year into the COVID-19 pandemic, we identified a strong negative association between stress and mental HRQOL, while pain was strongly negatively associated with physical HRQOL.